2011
DOI: 10.1097/tp.0b013e31822dc34f
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Nonadherence and Acute Rejection With Variation in Blood Immunosuppressant Levels in Pediatric Renal Transplantation

Abstract: The TAC CV% seems to be a useful and superior marker, compared with SD alone, for assessing medication nonadherence and the possibility of allograft rejection in pediatric renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
142
5
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(170 citation statements)
references
References 10 publications
20
142
5
3
Order By: Relevance
“…As early as 2000, Kahan et al 71 demonstrated that patients in a higher-variability cyclosporine cohort exhibited a higher incidence of graft loss compared with patients in the lower-variability cohort. Similar findings regarding the impact of cyclosporine variability on long-term outcomes were also reported by Waiser et al 72 In a study of 46 pediatric transplant recipients, higher variability of tacrolimus exposure was associated with the presence of acute rejection, 30 and Borra et al 31 reported a significant relationship between high within-patient variability of tacrolimus exposure and long-term graft failure. Furthermore, in a recent study of 220 kidney transplant recipients, higher tacrolimus intrapatient variability predicted accelerated progression of chronic histologic lesions before onset of renal dysfunction.…”
Section: Variability Of Immunosuppressive Exposure In Kidney Transplasupporting
confidence: 69%
See 1 more Smart Citation
“…As early as 2000, Kahan et al 71 demonstrated that patients in a higher-variability cyclosporine cohort exhibited a higher incidence of graft loss compared with patients in the lower-variability cohort. Similar findings regarding the impact of cyclosporine variability on long-term outcomes were also reported by Waiser et al 72 In a study of 46 pediatric transplant recipients, higher variability of tacrolimus exposure was associated with the presence of acute rejection, 30 and Borra et al 31 reported a significant relationship between high within-patient variability of tacrolimus exposure and long-term graft failure. Furthermore, in a recent study of 220 kidney transplant recipients, higher tacrolimus intrapatient variability predicted accelerated progression of chronic histologic lesions before onset of renal dysfunction.…”
Section: Variability Of Immunosuppressive Exposure In Kidney Transplasupporting
confidence: 69%
“…High variability of tacrolimus exposure is also considered to be a modifiable risk factor for kidney transplant recipients and has been associated with an increased risk of rejection and poor graft survival. 30,31 Another modification of our beliefs has been the assessment of patients who are nonadherent to treatment, and this is continuing to evolve. Fifteen years ago, we believed that most transplant recipients were adherent.…”
Section: The Kidney Graft Journey and Risk Managementmentioning
confidence: 99%
“…[18] Least squares means will be calculated for each group and the difference between the group means will be reported with a two-sided 95% confidence interval (CI). If the upper limit of the CI for the difference between the adjusted means (transition minus standard) for the therapy effect is less than 0, then lower variability in immunosuppressive agent levels and thus better adherence to therapy due to the new transition model is therefore proved.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Sapir-Pichhadze et al observed that a higher Tac IPV was associated with more late allograft rejection, transplant glomerulopathy, graft loss, and death with a functioning transplant [50]. In pediatric kidney transplantation, a high Tac IPV has also been associated with increased late rejection and graft loss [51,52].…”
Section: Intrapatient Variabilitymentioning
confidence: 99%